PERBANDINGAN EFISIENSI SEL FOTOVOLTAIK BERBASIS DSSC DARI EKSTRAK ZAT WARNA SEGAR DAN KERING TUMBUHAN SECANG, TARUM DAN PACAR KUKU - Patunrengi, Iswadi Ibrahim; Aisyah, Aisyah (Teknosains: Media Informasi Sains dan Teknologi, 2020)
Solar energy is the most abundance energy source in the world. However, it is used only limited amount for energy conversion. Photovoltaics system is one method to harvest energy from the sun and convert it to electricity. In this research, the fresh and dried extract of organic dyes from Secang wood; Tarum leaves (Indigofera tinctoria) and Pacar Kuku leaves (lawsonia inermis L) are used as a sensitizer in solar cells. Results shows that efficiency of photovoltaic cells from fresh extract are higher than the dried one. The efficiency of fresh dyes from Secang, Tarum and Pacar Kuku are 1,26%; 0,74% and 0,21% respectively. Meanwhile, efficiency of dried extracts are 1,26%; 0,74% and 0,21% respectively.